HST STIS Observations of the Central Radio/X-Ray Source in the Compact Starburst Galaxy Henize 2-10. Issue Volume 14:Issue S344(2019) (August 2018) - Rohr, Eric; Whittle, Mark; Reines, Amy; Johnson, Kelsey
Abstract: Based on radio and X-ray observations, it has been suggested that a black hole of mass ∼10 6 Mʘ resides in the dwarf starburst galaxy Henize 2-10. This unusual finding has important implications for the formation of massive black holes in the early universe since Henize 2-10 can be viewed as a low redshift analog to the first high- z galaxies. We present long-slit HST STIS spectra that include the central radio/X-ray source. While recent VLT-MUSE spectroscopic observations with 0″.7 seeing show no change in ionization near the central source, our higher spatial resolution STIS observations identify a distinct compact region at the location of the radio/X-ray source. Initial analysis reveals broader (FWHM ∼ 380 km s -1 ) blue-shifted lines of low ionization. Our analysis focuses on testing two scenarios: a LINER-like AGN and a young (few decades) SNR.